PERTUMBUHAN AYAM KAMPUNG SUPER YANG DIBERI PAKAN MENGANDUNG TEPUNG KUNYIT - Non Octa Trianty; Fahria Datau (Gorontalo Journal of Equatorial Animals, 2022)
The purpose of this study was to analyze the performance of the starter phase of super free-range chicken fed turmeric flour rations.This research was carried out from June to August 2020 at the Poultry Laboratory, Faculty of Agriculture, State University of Gorontalo. A total of 80 super free-range chickens aged 1 day were used as research objects, using the Completely Randomized Design (CRD) method. The average weight gain, consumption and conversion of each treatment were: 103.85 g, 285.03g, 2.74 (P0); 99.16g, 275.49g, 2.78 (P1); 109.16g, 283.10g , 2.60 (P2); and 98.51g, 109.16g, 2.78(P3). These results illustrate that the provision of turmeric flour in the ration has no effect on super free-range chickens during their growth period. Super free-range chickens in the starter phase can be given turmeric flour up to 6% in their rations.